Differential regulation by phosphatidylinositol 4,5-bisphosphate of pituitary plasma-membrane and cytosolic phosphoinositide kinases. - Imai, A (1986)
Regulation of phosphatidylinositol kinase (EC 2.7.1.67) and phosphatidylinositol 4-phosphate (PtdIns4P) kinase (EC 2.7.1.68) was investigated in highly enriched plasma-membrane and cytosolic fractions derived from cloned rat pituitary (GH3) cells. In plasma membranes, phosphatidylinositol 4,5-bisphosphate [PtdIns(4,5)P2] added exogenously enhanced incorporation of [32P]phosphate from [gamma-32P]MgATP2- into PtdIns(4,5)P2 and PtdIns4P to 150% of control; half-maximal effect occurred with 0.03 mM exogenous PtdIns(4,5)P2. Exogenous PtdIns4P and phosphatidylinositol (PtdIns) had no effect. When plasma membranes prepared from cells prelabelled to isotopic steady state with [3H]inositol were used, there was a MgATP2- dependent increase in the content of [3H]PtdIns(4,5)P2 and [3H]PtdIns4P that was enhanced specifically by exogenous PtdIns(4,5)P2 also. Degradation of 32P- and 3H-labelled PtdIns(4,5)P2 and PtdIns4P within the plasma-membrane fraction was not affected by exogenous PtdIns(4,5)P2. Phosphoinositide kinase activities in the cytosolic fraction were assayed by using exogenous substrates. Phosphoinositide kinase activities in cytosol were inhibited by exogenously added PtdIns(4,5)P2. These findings demonstrate that exogenously added PtdIns(4,5)P2 enhances phosphoinositide kinase activities (and formation of polyphosphoinositides) in plasma membranes, but decreases these kinase activities in cytosol derived from GH3 cells. These data suggest that flux of PtdIns to PtdIns4P to PtdIns(4,5)P2 in the plasma membrane cannot be increased simply by release of membrane-associated phosphoinositide kinases from product inhibition as PtdIns(4,5)P2 is hydrolysed.